(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
The structural behaviour of reinforced concrete buildings having equal overall height is remarkably influenced by their storey configuration. This paper examines how variations in the number of storeys affect the seismic response of reinforced concrete multistorey buildings while maintaining the same overall height. In this paper, five analytical models with 5-storey, 6-storey, 7-storey, 8-storey, and 9-storey building models were developed, considering both square and rectangular plan layouts to ensure representative structural modeling. However, the primary comparison is based on this building model with each other. The developed building models were analysed by help of computerbased software ETABS v22.6.0 using response spectrum analysis method in accordance with the provisions of NBC 105:2020 code. This study focuses on seismic response parameters like base shear, inter-storey drift, fundamental time period, storey stiffness, column axial force, and minimum reinforcement demand for columns and beams. The results indicate that increasing the number of storeys while keeping the overall height same leads to a longer fundamental time period and a reduction in lateral stiffness, higher inter-storey drift. Also, building experience relatively higher base shear, column axial forces, and influencing the reinforcement requirement. These trends remain consistent across both plan layouts, highlighting the dominant effect of storey configuration on structural behaviour. Overall, the study demonstrates that even when the total building height is same with different number of storeys noticeably affects seismic performance. The findings help professionals to create safer and more effective earthquakeresistant structures by optimising the design of reinforced concrete buildings and guaranteeing adherence to NBC 105:2020 code based seismic design guidelines.